Incentives to work: The case of Germany - Alfred Boss; Thomas Elendner (Kiel Institute for World Economics (IfW), 2005)
Based on a description of the German system of taxes and transfers, the incentives to work are analyzed for several groups of the labor force. The effects of the "Hartz IV" reform (effective from 2005 onwards) on the incentives receive particular attention. It turns out that the marginal (explicit and implicit) tax rates for most groups of the labor force remain high. It is concluded that employment probably will not be affected significantly by that part of the reform which aims at strengthening the incentives to work. Other elements of "Hartz IV" are only touched on. – Based on a description of the German system of taxes and transfers, the incentives to work are analyzed for several groups of the labor force. The effects of the ?Hartz IV? reform (effective from 2005 onwards) on the incentives receive particular attention. It turns out that the marginal (explicit and implicit) tax rates for most groups of the labor force remain high. It is concluded that employment probably will not be affected significantly by that part of the reform which aims at strengthening the incentives to work. Other elements of ?Hartz IV? are only touched on.
Keywords: H24; 330; Contributions to social security; Unemployment benefits; Implicit tax rates; Incentives to work; Income tax rates; Arbeitsangebot; Ökonomischer Anreiz; Steuerbelastung; Sozialversicherungsbeitrag; Arbeitslosenversicherung; Reform; Wirtschaftspolitische Wirkungsanalyse; Deutschland